Brazilian and Foreign Education (A brief history of internationalization of studies in Brazil) - Amorim, Marina Alves (Lembaga KITA, 2022)
: In this study, we propose a brief history of the internationalization of studies in Brazil, from colonial times to the present, and we try to glimpse the reasons for this phenomenon. By doing so, we show how the study abroad period is a deeply entrenched cultural practice among Brazilians and that can only be understood if we take into account the place traditionally occupied by foreigners in the reproduction process of local elites. During the development of doctoral research, we analyzed the trajectory of eight Brazilian students who are studying or have studied in France. This study allows us to glimpse at how the phenomenon of internationalization of studies, discussed in this text, from its macro-social perspective, is experienced on an individual scale. Certain stories also reveal that Brazilians traveling to study abroad are generally attracted to a valuable education and experience in Brazil, in the educational, professional and social markets, which does not necessarily mean better quality. Immersed in the process of dismissing diplomas, as a result of another process, namely the